Implementasi Akad Pembiayaan Qard dan Wakalah bil Ujrah pada Platform Fintech Lending Syariah ditinjau Berdasarkan Peraturan Otoritas Jasa Keuangan (OJK) dan Fatwa DSN-MUI - Sri Maulida; Ahmadi Hasan; Masyitah Umar (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The purpose of this research is to analyze the implementation of Qard and Wakalah bil Ujrah financing contract for Sharia Lending Platform reviewed based on regulation of Otoritas Jasa Keuangan (OJK) and Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI). The method of approach used in this research is a method of empirical approach that is legal research on the enforcement or implementation of normative provisions in action at any particular legal event occurring in the community. The results showed that the information system with Sharia invoice financing used by sharia Investree Platform is according to review based on regulation of OJK No. 77/POJK.01/2016 in chapter IV of article 19 of the financing agreement on lending services based on information technology with Lenders. Secondly, the implementation of Akad Al qordh used by Sharia Investree Platform has been reviewed according to the Fatwa DSN MUI No. 19/DSN-MUI/IV/2001 on Al-Qardh. Thirdly, the implementation of Akad Wakalah bil Ujrah used by Sharia Investree Platform has been reviewed according to Fatwa DSN-MUI No. 113/DSN-MUI/IX/2017 on Akad Wakalah Bi Al-Ujrah which is devoted to the Fatwa DSN-MUI No. 67/DSN-MUI/III/2008 on Islamic debt factoring. Fourth, the classification of QARDH and Wakalah bil Ujrah that used by the sharia Investree Platform is using a factoring financing model reviewed by the Fatwa DSN-MUI No. 117/DSN-MUI/II/2018 on information technology-based financing services based on Islamic principles.